Up regulation of A2B adenosine receptor on monocytes are crucially required for immune pathogenicity in Indian patients exposed to Leishmania donovani. (March 2016) - Vijayamahantesh; Amit, Ajay; Kumar, Santosh; Dikhit, Manas R.; Jha, Pravin K.; Singh, Ashish K.; Sinha, Kislay K.; Pandey, Krishna; Das, V.N.R.; Das, Pradeep; Bimal, Sanjiva
Graphical abstract: Highlights: Up-regulation of A2B receptor was observed in Indian VL patient. Adenosine promotes the disease progression through ERK and STAT3 pathway. Up-regulation of A2B receptor is co-related with disease severity. Abstract: Adenosine, an endogenous purine nucleoside is one such extracellular signalling molecule whose role in regulation of anti-inflammatory cytokines and immune pathogenicity in visceral leishmaniasis is not fully understood. Here, we investigated the relationship between Leishmania donovani infection and expression of A2B receptor on monocytes in VL patients in their pre and post treatment stage. We also investigated the molecular mechanisms influencing the interaction between immunopathogenicity and infection by exposing Leishmania donovani pulsed macrophages to Adenosine. A direct correlation of up-regulated A2B expression on monocytes with increased parasite load was also observed. Our results also suggested that A2B receptor activation is critically required for the stimulatory effect of adenosine on IL-10 production and suppression of nitric oxide release. The stimulatory effect of adenosine on Leishmania donovani induced IL-10 production required ERK1/2 activation and is p-38 MAPK independent.